Identifying crucial indicators for successful homework completion: importance-performance analysis - Abdul Rahman, Madina; Khairani, Ahmad Zamri (Journal of Education and Learning (EduLearn), 2025)
Successful homework completion necessitates engagement in self-regulated learning activities. The key challenge lies in fostering self-confidence among students to enable them to complete homework independently. Applying the importance-performance theory, the study uses a unique statistical tool to assess homework completion for practical recommendations. The objective is to offer practical recommendations benefiting students, parents, teachers, schools, and the Ministry of Education, aimed at enhancing homework completion due to its established benefits. Surveys encompassed 970 high school students in Penang’s northern state. Data underwent analysis via SmartPLS software, utilizing its importance performance functionality. Outcomes highlight the significance and performance of expectancy, value, homework management, homework effort constructs, and their indicator variables. These aspects were assessed within the importance-performance map analysis (IPMA). The homework effort construct notably exhibited the most pronounced influence on homework completion. Encouragingly, students are advised against copying mathematics homework and instead encouraged to complete it autonomously. Both homework effort and value constructs received a “keep up” endorsement, while homework management and expectancy constructs garnered an “education” recommendation. This approach yields a user-friendly visual tool to evaluate homework aspects. It effectively steers stakeholders in pinpointing pivotal areas for augmenting homework completion.